2015
DOI: 10.1021/acs.jpcc.5b08009
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Stability of Hydrogen-Bonded Networks of Bridged Triphenylamines on Au(111) and Cu(111)

Abstract: The adsorption, chemical nature, and self-assembly of diaminotriazinyl- and carboxyl-substituted triphenylamines with dimethylmethylene bridges were studied on Au(111) and Cu(111) at submonolayer coverage by low-temperature scanning tunneling microscopy and density functional theory. On Au(111), both molecules form extended porous honeycomb networks. The geometry of the networks agrees well with density functional theory optimized hydrogen-bonded gas phase structures. Therefore, the self-assemblies on Au(111) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…[10] Exploiting the rich chemistry of aromatic amines,b ack in the 1980s, Hellwinkel and Melan [11] reported an elegant molecular design resulting from the exhaustive introductiono fb ridging units at the ortho-position of triphenylamine, which forces the originally propeller-shaped scaffold into av irtually planar geometry (Figure 1b). [12] Various types of bridged triphenylamines have been reported to date, [12,13] including carbonyl, [14] ether, [5,15,16] thioether, [17] dimethylmethylene, [18,19] and diphenylmethylene bridges [20] as well as triphenylamines with two fused pentagons. [21] It has been demonstrated that Hellwinkel's design principle can be adopted to stabilize N-centered radicalcations by delocalization of the radical over the planarized p-system.…”
mentioning
confidence: 99%
“…[10] Exploiting the rich chemistry of aromatic amines,b ack in the 1980s, Hellwinkel and Melan [11] reported an elegant molecular design resulting from the exhaustive introductiono fb ridging units at the ortho-position of triphenylamine, which forces the originally propeller-shaped scaffold into av irtually planar geometry (Figure 1b). [12] Various types of bridged triphenylamines have been reported to date, [12,13] including carbonyl, [14] ether, [5,15,16] thioether, [17] dimethylmethylene, [18,19] and diphenylmethylene bridges [20] as well as triphenylamines with two fused pentagons. [21] It has been demonstrated that Hellwinkel's design principle can be adopted to stabilize N-centered radicalcations by delocalization of the radical over the planarized p-system.…”
mentioning
confidence: 99%
“…The tip-to-side bonding motif of the DAT head group has two bonding options, which leads to an organisational chirality, where homochiral domains with left-handed and right-handed chirality were observed. 8 In contrast, the homomolecular CDTPA network is symmetric. However, the binary ADTPA+CDTPA network also bears the possibility of organisational chirality, since it has an asymmetric tip-to-tip bonding motif, see Fig.…”
Section: Organisational Chirality Of the H-bonded Networkmentioning
confidence: 99%
“…The global energy minima are twisted, 3-dimensional configurations due to the preferred out-ofplane tilt of the amino groups (see Ref. [8] for details). In Table S1 we refer to the two structural alternatives as "planar" and "twisted".…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…One stratagem that has been developed is to first scrutinize such interactions in a chemical environment without solvent or mixing effects, thereby allowing the system to evolve under the guidance of the most thermodynamically stable interactions between precursor molecules; this can be achieved by letting the two molecules directly interact with each other through self-assembly under ultrahigh vacuum (UHV) on a substrate. ,, UHV surface deposition experiments allow the precursors to “naturally” self-assemble without solvent, but are of course influenced by the substrate itself. Au(111) substrates have often been shown, however, to have a uniform effect on the potential energy surfaces of adsorbed hydrogen-bonded molecular networks, often creating networks that would be predicted in the absence of surface-adsorbate interactions. ,, This indicates that Au(111) is a useful template for such experiments, and Au(111) further allows for the use of scanning tunneling microscopy (STM) to probe the new crystals and determine their self-assembled structures. Even though the surface will restrict the molecular assembly by forcing it to occur at the interface, the characterization of any mixed-composition molecular network would indicate a degree of thermodynamically stable interaction between the molecular precursors (vs the interactions among the separate components).…”
Section: Introductionmentioning
confidence: 99%